2022
DOI: 10.37934/araset.28.2.222234
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic of Copper-Aluminium of Oxide Hybrid Nanoparticles Containing Gyrotactic Microorganisms over a Vertical Cylinder with Suction

Abstract: The boundary layer flow with heat and mass transfer are important since the quality of final product depends on factors such as the rate of cooling and stretching phenomenon. The pivotal aim of this research is to address magnetohydrodynamics (MHD) copper-aluminium oxide hybrid nanoparticles containing gyrotactic microorganisms over a stretching vertical cylinder with suction. The mathematical model has been formulated based on Tiwari-Das nanofluid model. Two types of nanofluid containing Copper (Cu) and Alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In a different study, Soid et al, [31] investigated the effects of hybrid nanofluids, comprising copper-aluminum oxide hybrid nanoparticles with gyrotactic microorganisms, over a stretching vertical cylinder with suction. The inclusion of both types of nanoparticles increased the thermal conductivity and heat transfer coefficients of hybrid nanofluid in comparison to base fluid, making it faster in terms of transit rate than nanofluid.…”
Section: Fig 5 Some Advantages and Disadvantages Of Hybrid Nanofluidsmentioning
confidence: 99%
“…In a different study, Soid et al, [31] investigated the effects of hybrid nanofluids, comprising copper-aluminum oxide hybrid nanoparticles with gyrotactic microorganisms, over a stretching vertical cylinder with suction. The inclusion of both types of nanoparticles increased the thermal conductivity and heat transfer coefficients of hybrid nanofluid in comparison to base fluid, making it faster in terms of transit rate than nanofluid.…”
Section: Fig 5 Some Advantages and Disadvantages Of Hybrid Nanofluidsmentioning
confidence: 99%
“…In the year 2022, the study of the nanofluids with the presence of MHD effect by Rosaidi et al (2022), Nayan et al (2022), Bosli et al (2022), andIshak et al (2022) found that with the effect of the magnetic field increase the heat transfer as well as the velocity of the study. Study on the MHD effect was discovered in different situations by some researchers such as Ilias (2018), Ahmad et al (2019), Khashi'ie et al (2019), and Soid et al (2022.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that heat transfer enhancement increases by increasing of hybrid nanofluid volume concentration and volume flow rate. Recently, the study of hybrid nanofluids on flow over various situations was considered by researchers, such as over a vertical, solid sphere, stretching/shrinking sheet, bioconvection and others [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%